2015
DOI: 10.1016/j.rser.2015.07.053
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Wind Energy Systems: A review of the technologies

Abstract: Among novel technologies for producing electricity from renewable resources, a new class of wind energy converters has been conceived under the name of Airborne Wind Energy Systems (AWESs). This new generation of systems employs flying tethered wings or aircraft in order to reach winds blowing at atmosphere layers that are inaccessible by traditional wind turbines. Research on AWESs started in the mid seventies, with a rapid acceleration in the last decade. A number of systems based on radically different conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
167
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(197 citation statements)
references
References 41 publications
1
167
0
7
Order By: Relevance
“…Com o trabalho de Loyd [2], um importante passo foi dado nessa direção. Implementações sérias de protótipos, contudo, só apareceram naúltima década, quando materiais leves e resistentes o suficiente para suportar as forças atuando tanto na pipa quanto na corda foram desenvolvidos [3,6,11,12,13]. Além disso, por ser um sistema instável e sensívelàs variações ambientais, a pipa necessita de um controle automático sofisticado, que exige recursos de navegação e sensoriamento que só recentemente se tornaram disponíveis.…”
Section: Produção De Energia Elétrica Por Meio De Pipasunclassified
“…Com o trabalho de Loyd [2], um importante passo foi dado nessa direção. Implementações sérias de protótipos, contudo, só apareceram naúltima década, quando materiais leves e resistentes o suficiente para suportar as forças atuando tanto na pipa quanto na corda foram desenvolvidos [3,6,11,12,13]. Além disso, por ser um sistema instável e sensívelàs variações ambientais, a pipa necessita de um controle automático sofisticado, que exige recursos de navegação e sensoriamento que só recentemente se tornaram disponíveis.…”
Section: Produção De Energia Elétrica Por Meio De Pipasunclassified
“…Several private companies, universities, and public research centres were able to realize and control some small-scale High Altitude Wind Energy Systems. The first HAWES prototype that successfully produced some energy, using a 5 m A quite comprehensive review of HAWES technologies can be found in a recent paper by Cherubini et al [18]. Many different technologies were proposed for the exploitation of high altitude wind, divided in two main classes, with electric generation at a ground station (groundgen), and with onboard generation (flygen).…”
Section: Issue1: Inconvenience Of Loyd Modelmentioning
confidence: 99%
“…While there are numerous studies on wind characteristics near the surface, such studies at higher altitudes are rare due to the lack of specific practical applications. However, with recent advances in high altitude wind power (HAWP) technologies [6], characterisation of higher-level winds could take on greater importance. In addition, it is a trivial fact in aviation operations that en-route winds are a major determinant of flight duration and fuel burn [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is given by Equation (6). The two expressions given in Equation (6) are equivalent because the trace is an invariant of a tensor.…”
mentioning
confidence: 99%